2018
DOI: 10.1002/anie.201710731
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Difluoromethylthioesters from Aldehydes

Abstract: Difluoromethylthioester compounds are yet another important kind of organofluorine compound and are reported here for the first time. They can be efficiently synthesized from various aldehydes. The synthetic method features mild reaction conditions, good tolerance of functional groups, broad substrate scope, and importantly, no metal is involved in the reaction. The approach has the potential to become an important tool for the late-stage functionalization of advanced synthetic intermediates, and should have m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 73 publications
0
22
0
3
Order By: Relevance
“…In the presence of radical-clock type reagent, the ring-closure product was isolated (81b). Based on these preliminary results and previous literature, 145,[183][184][185][186][187][188][189][190] we proposed a radical mechanism, in which the difluoromethylthiyl radical was generated from either the homolysis event of…”
Section: Photo-induced C Sp2 -H Difluoromethylthiolation: Synthesis Omentioning
confidence: 58%
“…In the presence of radical-clock type reagent, the ring-closure product was isolated (81b). Based on these preliminary results and previous literature, 145,[183][184][185][186][187][188][189][190] we proposed a radical mechanism, in which the difluoromethylthiyl radical was generated from either the homolysis event of…”
Section: Photo-induced C Sp2 -H Difluoromethylthiolation: Synthesis Omentioning
confidence: 58%
“…The Wang group also reported a radical difluoromethylthiolation of aldehydes with PhSO 2 SCF 2 H (R3) (Scheme 18). 39 Various aryl, heteroaryl, alkyl, and alkenyl aldehydes could all be converted into the expected products, demonstrating a wide substrate scope. They proposed that t-BuOOH could directly abstract a hydrogen atom from aldehydes to generate a carbonyl radical.…”
Section: Scheme 17 Difluoromethylthiolation Of Aldehydes With Phso 2 mentioning
confidence: 99%
“…In 2018, Wang and co-workers communicated the first example of direct thioesterification of aldehydes with aromatic thiosulfonates [62]. They showed that treatment of various aromatic, heteroaromatic, aliphatic, and α,β-unsaturated aldehydes 47 with commercially available PhSO 2 SCF 2 H as an efficient source of medicinally important SCF 2 H group in the presence of 2 equiv.…”
Section: Fluoroalkylation Of Aldehydes With Arso 2 Sr F Reagentsmentioning
confidence: 99%